EXPANDING COMPULSORY ENFORCEMENT OF EVICTION JUDGEMENT TO THIRD PARTIES NOT PARTICIPATED IN LITIGATION - Gevorgian, Garik (State and Law, 2022)
In this article the author examines peculiarities of enforcing court decisions on the recovery of immovable property from illegal possession in the Republic of Armenia. The stage of enforcement is crucial in the process of protecting rights, particularly relevant to claims for awarding, such as vindicatory claims, which involve compelling the defendant to perform factual actions, such as transferring the property to the owner. Specifically, the article examines legislative provisions authorizing the enforcement service to evict not only the addressee of the court decision but also third parties who do not have registered property rights. The extension of the court's eviction decision to third parties gives reason to believe that absolute protective legal relationships arise between the owner and an indefinite circle of individuals who illegally possess the property at the time of enforcement, while the prevailing position in legal science is that protective legal relationships always have a relative nature. These provisions are considered in light of the principle of the binding nature of judicial acts only for the participants in the judicial process and due process of law constitutional guarantee.
Keywords: vindication claim; eviction claim; compulsory enforcement; right to property; factual possession; adverse possession; immovable property; registration of rights